ChemInform Abstract: Magnesium‐Promoted Reductive Acylation of Aromatic Conjugated Ynones Accompanying with Transposition of the Triple Bond. Issue 33 (August 2015) - Zhang, Tianyuan; Takano, Atsushi; Nishiyama, Yutaro; Maekawa, Hirofumi
Abstract Byproducts of type (IV) are obtained in most cases in less than 20% yield.